PILIHAN DIKSI DALAM KONTESTASI PILPRES 2024 DALAM PERSPEKTIF ANALISIS WACANA KRITIS SEBAGAI PENINGKATAN MUTU PENDIDIKAN LITERASI - Ni nyoman ayu suciartini; Payuyasa, I Nyoman (Jurnal Penjaminan Mutu, 2024)
The diction or terms used in the 2024 presidential election battle are some deliberately coined, while others emerge inadvertently, which can lead to multiple interpretations and meanings. Candidate pairs and, on the other hand, can also decrease electability in the political atmosphere. This study aims to analyze popular diction in the 2024 presidential election, both from social media and the bustling reality in society. This research employs a qualitative descriptive research design with the assistance of data collection methods such as observation, documentation, and literature review. The analytical tool used is Discourse Analysis. The results of this study indicate that the most popular diction often contains meanings that, when dissected using critical discourse analysis, reveal several perspectives related to the significance of the diction. Terms such as "slepet", "samsul", "cawe-cawe", are the most popular diction that influences both social media and the real world. Many posts are inspired by the diction of the 2024 presidential election, which certainly contains certain political meanings. The choice of diction or language by a leader figure greatly determines the process of garnering votes. Recorded in the diction that emerges in the presidential election, this diction can become an advertisement in another form that contributes to increasing electability